2013
DOI: 10.1080/09658211.2013.789914
|View full text |Cite
|
Sign up to set email alerts
|

Escaping mental fixation: Incubation and inhibition in creative problem solving

Abstract: The inhibition underlying retrieval-induced forgetting has been argued to play a crucial role in the ability to overcome interference in memory and cognition. Supporting this conjecture, recent research has found that participants who exhibit greater levels of retrieval-induced forgetting are better at overcoming fixation on the Remote Associates Test (RAT) than are participants who exhibit reduced levels of retrieval-induced forgetting. If the ability to inhibit inappropriate responses improves the ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
24
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 28 publications
(31 reference statements)
6
24
1
1
Order By: Relevance
“…When problems were not fixated, participants exhibiting low levels of retrievalinduced forgetting performed just as well as participants exhibiting high levels of retrieval-induced forgetting. Koppel and Storm (2014) observed a similar pattern of results, showing once again that retrieval-induced forgetting correlates with problem-solving success for fixated RAT problems, but that the correlation is eliminated when participants are given an incubation period after an initial problem-solving attempt, thus allowing fixation to dis sipate on its own and presumably obviating the need for inhibition during the subsequent problem-solving attempt.…”
Section: Overcoming Fixation Via Inhibitionsupporting
confidence: 72%
“…When problems were not fixated, participants exhibiting low levels of retrievalinduced forgetting performed just as well as participants exhibiting high levels of retrieval-induced forgetting. Koppel and Storm (2014) observed a similar pattern of results, showing once again that retrieval-induced forgetting correlates with problem-solving success for fixated RAT problems, but that the correlation is eliminated when participants are given an incubation period after an initial problem-solving attempt, thus allowing fixation to dis sipate on its own and presumably obviating the need for inhibition during the subsequent problem-solving attempt.…”
Section: Overcoming Fixation Via Inhibitionsupporting
confidence: 72%
“…They reasoned that individuals showing higher 382 ANGELLO, STORM, SMITH levels of RIF should be better at solving RAT problems negatively primed with incorrect associates. Consistent with this conjecture, a positive correlation between RIF and RAT problem solving was observed, indicating that proficiency in memory inhibition during a memory retrieval task is associated with the ability to overcome fixation during creative problem solving (see also , Koppel & Storm, 2013;Storm, 2011). Subsequent research has found that participants who forget incorrect associates following problem solving are also better at overcoming fixation and correctly solving negatively primed RAT problems (Storm, Angello, & Bjork, 2011).…”
Section: Memory Inhibitionsupporting
confidence: 56%
“…Smith and Blankenship () found correlational evidence consistent with the forgetting fixation hypothesis; longer delays improved re‐test performance on initially unsolved insight problems, and delays also decreased recall of words (blockers) used initially to block problem‐solving. Furthermore, experimentally reducing the accessibility of blockers via directed forgetting (Koppel & Storm, ) or via repeated suppression (Angello et al., ) improved performance on verbal insight problems; forgetting blockers benefited resolution of unsolved insight problems. These studies provide experimental evidence of the forgetting fixation hypothesis.…”
Section: The Present Experimentsmentioning
confidence: 99%